2016
DOI: 10.1126/sciadv.1501882
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional GaSe/MoSe 2 misfit bilayer heterojunctions by van der Waals epitaxy

Abstract: Synthesized two-dimensional GaSe/MoSe2 misfit heterostructures form p-n junctions with a gate-tunable photovoltaic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
205
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(209 citation statements)
references
References 45 publications
3
205
1
Order By: Relevance
“…Li et al achieved a GaSe/MoSe 2 heterojunction through a two‐step growth process and fabricated a photodetector by patterning a source–drain contact on a monolayer MoSe 2 flake partially covered by monolayer GaSe domains, as shown in Figure c. Under white‐light illumination, the device exhibited a stable photoresponse with an ON/OFF ratio up to 215 and a reproducible photoresponsivity of ≈30 mA W −1 . Besides direct CVD growth vertical heterojunctions, in‐plane heterojunctions have also been investigated by Duan et al, as shown in Figure d.…”
Section: Strategies For Enhancing the Performance Of Photodetectorsmentioning
confidence: 99%
“…Li et al achieved a GaSe/MoSe 2 heterojunction through a two‐step growth process and fabricated a photodetector by patterning a source–drain contact on a monolayer MoSe 2 flake partially covered by monolayer GaSe domains, as shown in Figure c. Under white‐light illumination, the device exhibited a stable photoresponse with an ON/OFF ratio up to 215 and a reproducible photoresponsivity of ≈30 mA W −1 . Besides direct CVD growth vertical heterojunctions, in‐plane heterojunctions have also been investigated by Duan et al, as shown in Figure d.…”
Section: Strategies For Enhancing the Performance Of Photodetectorsmentioning
confidence: 99%
“…2,3 Because the interlayers of GaSe crystal are connected via van der Waals bonds, it can be exfoliated to few layer or even monolayers for further device application. 4 It means that GaSe could be considered as a exible material even while it is exfoliated from thick to thin multilayers. For light-emitting capability, unlike MoSe 2 which has only enhanced photoluminescence (PL) efficiency as a monolayer, the PL intensity of monolayer GaSe vanishes, and increases with the layer thickness increasing to multilayer or bulk form.…”
Section: Introductionmentioning
confidence: 99%
“…4,13 Among those methods, strain engineering is more attractive and applicable when a exible optoelectronics device is under normally-operated condition. Our previous research has found that the mechanical bending would also enhance the light intensity of photoluminescence peak of 2D InSe layered semiconductor.…”
mentioning
confidence: 99%
“…Furthermore, by sandwiching graphene (g) in an atomically thin MoS 2 –WSe 2 p–n junction (forming a p–g–n heterostructure), the spectral range can be broadened to the infrared regime due to the gapless nature of the graphene . In addition to the most studied MoS 2 /WSe 2 vdW heterojunction, vertical heterostructures based on other 2D crystals, such as BP/MoS 2 , WSe 2 /MoSe 2 , α‐MoTe 2 /MoS 2 , SnS 2 /MoS 2 , GaTe/MoS 2 , GaSe/MoSe 2 , ReS 2 /ReSe 2 , MoS 2 /Bi 2 Te 3 , and MoS 2 /WS 2 /WSe 2 , have also been explored for their potential in photovoltaics. Particularly, TMDCs can be assembled with organic materials for efficient 2D‐based solar cells.…”
Section: Photovoltaics In a Vertical Configuration Of 2d Materialsmentioning
confidence: 99%